1987
DOI: 10.1002/pssa.2211000108
|View full text |Cite
|
Sign up to set email alerts
|

On the intrinsic gettering in Fe-contaminated CzSi

Abstract: Oder)') ( a ) and Z~~t r a l~n s~i t u t fur Kernforschung der Akademie der Wissenschaften der D D R , Rossendorf2) (b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…[6], the data on the effect of iron on nucleation of silicon-oxide precipitates are contradictory. However, everyone agrees that iron enhances the final stage of growth of silicon-oxide precipitates, i.e., the formation of OSFs [113,141,[145][146][147][148][149]. Fujino et al [147] showed that the density of OSFs increased by nearly 5 orders of magnitude as iron surface contamination level increased from 3×10 11 cm -3 to 10 13 cm -3 .…”
Section: Analysis Of the Current Understanding Of Iron In Siliconmentioning
confidence: 99%
“…[6], the data on the effect of iron on nucleation of silicon-oxide precipitates are contradictory. However, everyone agrees that iron enhances the final stage of growth of silicon-oxide precipitates, i.e., the formation of OSFs [113,141,[145][146][147][148][149]. Fujino et al [147] showed that the density of OSFs increased by nearly 5 orders of magnitude as iron surface contamination level increased from 3×10 11 cm -3 to 10 13 cm -3 .…”
Section: Analysis Of the Current Understanding Of Iron In Siliconmentioning
confidence: 99%